IMPLEMENTASI VIDEO TUTORIAL INTERAKTIF DALAM PEMBELAJARAN GERAKAN SHALAT PADA SISWA DI MADRASAH TSANAWIYAH NEGERI 5 KOTA JAMBI - Meichendha, Intan; surayya, Ely (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores the implementation of interactive video tutorials in teaching Islamic prayer (ṣalāh) movements to students at Madrasah Tsanawiyah Negeri 5 Kota Jambi. Mastery of prayer movements is a fundamental component of Fiqh learning, requiring not only cognitive understanding but also accurate practical performance. This research employed a qualitative descriptive approach, with data collected through classroom observations, in-depth interviews, and documentation. The participants consisted of the school principal, Fiqh teachers, and eighth-grade students.The findings reveal that interactive video tutorials significantly enhance students’ comprehension of prayer movements by providing clear visual demonstrations and structured learning sequences. The use of audiovisual media increased students’ engagement, motivation, and active participation during learning activities. Students were better able to imitate correct movements and distinguish between obligatory (arkān) and recommended (sunan) components of prayer. From the teachers’ perspective, interactive video tutorials facilitated clearer explanations and more efficient classroom management during practical sessions. Supporting factors for successful implementation included adequate learning facilities, teacher readiness, and students’ positive attitudes toward digital media. However, several challenges were identified, such as limited instructional time, technical constraints, and differences in students’ learning pace. Overall, the study concludes that interactive video tutorials are an effective instructional medium for improving the quality of Fiqh learning, particularly in teaching prayer movements, and they hold strong potential for broader application in Islamic religious education.